Compositionally gradient Al2O3–B4C/Al composites with interpenetrating structure and tailored properties via material extrusion-based additive manufacturing and pressure infiltration - Yu-Bai Hu; Ming-Yue Jiang; Ping Shen (Virtual and Physical Prototyping)
Traditional fabrication methods for metal–ceramic composites often struggle to achieve the level of control needed for material on-demand design and property optimisation, despite the potential for enhanced performance. This study presents a novel approach that overcomes these limitations by combining material extrusion-based additive manufacturing and pressure infiltration techniques, which enables the fabrication of compositionally graded Al2O3–B4C/Al layered composites with tailored properties. Precise control over the B4C/Al2O3 ratio allows for the fine-tuning of key mechanical properties, including bending strength, fracture toughness, and fracture work. The composites exhibit anisotropic behaviour, with performance influenced by the ceramic composition, loading direction, and layer spacing. A notable observation is the enhancement of damage tolerance through multi-crack propagation as the Al2O3 content in the ceramic layers increases. Additionally, wear tests demonstrate exceptional abrasion resistance, highlighting the synergistic effects of B4C hardness and Al2O3 toughness. This research establishes novel strategies for the design and fabrication of metal–ceramic composites with tailored properties, paving the way for their implementation in demanding applications where a combination of strength, toughness, and wear resistance is critical.